A bibliometric analysis of carbon and water footprints in renewable energy: The post-COVID-19 landscape - Khashayar Fardnia; Hossein Yousefi; Mahmood Abdoos (Green Technologies and Sustainability, 2025)
The recent energy crisis in Europe has underscored the urgent need for renewable energy sources to meet growing energy demands and mitigate environmental impacts. This study investigates the Carbon Footprint (CF) and Water Footprint (WF) associated with renewable energies, considering the effects of COVID-19. Data was sourced from Scopus documents published after 2019, using keywords such as “carbon footprint ”, “water footprint ”, “renewable energies” and “COVID-19.”Recent research increasingly focuses on the interplay between energy, environment, and water. Using data extracted from the Scopus database on countries, keywords, highly cited publications, and trending research topics, the bibliometric software VOS viewer has been employed to evaluate bibliographic entries. The findings reveal that the United States leads in the volume of publications within this field, with significant research also originating from China, the United Kingdom, and European Union countries. Among the 1834 articles analyzed, keywords associated with environmental impact, climate change, sustainable development, and fossil fuels were frequently linked to our search terms.This paper synthesizes literature on the correlation between CF and WF, identifies prevalent themes, and outlines potential directions for future research in this domain. The study addresses the urgent need for sustainable energy solutions amidst the ongoing energy crisis in Europe. The goals are to provide a comprehensive analysis of the impacts of renewable energy specially the environmental impacts, while highlighting the most researched areas and emerging trends in the field, and identify potential gaps in the existing literature to suggest areas for future research.